The role of milk urea nitrogen in nutritional assessment and its relationship with phenotype of dairy cows: A review - Xiaowei Zhao; Nan Zheng; Yangdong Zhang; Jiaqi Wang (Animal Nutrition)
Urea is a small molecule that can readily cross the blood-milk barrier into milk, leading to a strong correlation between blood urea nitrogen (BUN) and milk urea nitrogen (MUN) concentrations. Although MUN is a minor component of milk, it is a valuable and cost-effective tool to flag potential nutrition-related problems in dairy herds. Many studies have suggested that intake of dietary protein and energy, as well as their synchronized release in the rumen, are major factors influencing MUN concentration. Therefore, measuring MUN can serve as a valuable indicator for improving nutritional management in dairy herds. Both excessively high and low MUN values are undesirable for dairy cows due to their negative effects on reproductive performance, health, and nitrogen use efficiency. Moreover, research indicates that MUN is a trait with low to moderate heritability and is positively correlated to nitrogen excretion. However, there are still inconsistencies regarding selecting cows with a low MUN phenotype can effectively reduce nitrogen excretion and affect other economic traits in dairy cows. This paper provides an overview of MUN's utility in nutritional assessment, presents its relationship with economically important milk traits, reproductive performance, health, and nitrogen emissions. It also describes the backgrounds of the gastrointestinal microbiota, intestine and kidney physiology in cows with different MUN concentrations, aiming to further enhance our understanding of MUN and provide a reference for optimal diets of cows.